Texts and materials on international human rights - Smith, Rhona K. M. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Texts and Materials on International Human Rights offers a carefully tailored overview of the subject that covers sources and theories, institutions and structures, and substantive rights. The fourth edition is fully updated to include all key developments in the law, in particular issues around reform in the UN and the topical application of human rights around the world. This collection of materials offers a comprehensive overview of the institutional structures relevant to international human rights law, crucial to the understanding of how law works in this challenging area. Designed to guide students through the fundamental texts for this subject, the author's commentary contextualises each extract to explain its relevance, while highlighted further reading makes links to cutting edge academic commentary to provide next steps for student research. Offering a clear text design that distinguishes between materials and author commentary, and including reflective questions throughout to aid understanding, this book is ideal for students seeking to engage with the key issues in the study of International Human Rights"--
OCLC-licensed vendor bibliographic record.
Keywords: Human rights; Civil rights; LAW / General; LAW / International